Circular RNAs in Sudden Cardiac Death Related Diseases: Novel Biomarker for Clinical and Forensic Diagnosis - Meihui Tian; Zhipeng Cao; Hao Pang (Molecules, 2021)
The prevention and diagnosis of sudden cardiac death (SCD) are among the most important keystones and challenges in clinical and forensic practice. However, the diagnostic value of the current biomarkers remains unresolved issues. Therefore, novel diagnostic biomarkers are urgently required to identify patients with early-stage cardiovascular diseases (CVD), and to assist in the postmortem diagnosis of SCD cases without typical cardiac damage. An increasing number of studies show that circular RNAs (circRNAs) have stable expressions in myocardial tissue, and their time- and tissue-specific expression levels might reflect the pathophysiological status of the heart, which makes them potential CVD biomarkers. In this article, we briefly introduced the biogenesis and functional characteristics of circRNAs. Moreover, we described the roles of circRNAs in multiple SCD-related diseases, including coronary artery disease (CAD), myocardial ischemia or infarction, arrhythmia, cardiomyopathy, and myocarditis, and discussed the application prospects and challenges of circRNAs as a novel biomarker in the clinical and forensic diagnosis of SCD.